Esophageal Findings in the Setting of a Novel Preventive Strategy to Avoid Thermal Lesions during Hybrid Thoracoscopic Radiofrequency Ablation for Atrial Fibrillation - Rani Kronenberger (MDPI AG, 2021)
Purpose The development of an atrio-esophageal fistula, a rare yet potentially lethal complication of ablation for atrial fibrillation, could be related to direct tissue heat transfer during and immediately after the ablation. We therefore studied the postoperative esophageal findings by esophagogastroduodenoscopy in patients that underwent a hybrid ablation procedure using a novel preventive strategy to avoid thermal lesions. Methods Thirty-four patients (28 males; 65 years ± 9 years) were retrospectively included. All underwent a hybrid ablation in our center between April 2015 and November 2019 and agreed to an esophagogastroduodenoscopy within 0–14 days (mean: 5 days) following the ablation. To reduce the incidence of thermal lesions three procedural preventive strategies were introduced: (i) videoscopic intrathoracic transesophageal echocardiographic probe visualization to understand the relationship between posterior left atrial wall and esophagus, with probe retraction before ablation; (ii) lifting the cardiac tissue away from the esophagus during energy application; and (iii) a 30-s cool-off period after energy delivery with irrigation of the device, the ablated tissue, and the surrounding tissues. Results No esophageal thermal lesions were observed. One third of patients were diagnosed with incidental esophageal findings unrelated to the ablation procedure (11; 32.4%). Conclusion Novel preventive strategies by visualization and by avoiding contact between the ablation catheter or ablated tissue and the pericardium, seems to eliminate the potential risk of esophageal thermal lesions in the setting of hybrid ablation. Since one third of patients had preexisting esophageal disease, a more comprehensive pre-operative screening could be important to reduce the risk.